Anti‐N‐methyl‐D‐aspartate receptor encephalitis unresponsive to early and aggressive immunotherapy in a young female: A case report. Issue 4 (27th May 2020) - Kaur, Harleen; Mittal, Gaurav Kumar
Abstract: Background: Acute encephalitis refers to inflammation of the brain that develops as a rapidly progressive encephalopathy. It usually has an infectious origin, but an increasing number of autoimmune etiologies have been identified recently. Keeping a high index of suspicion is of great importance, because delayed diagnosis and delayed initiation of appropriate therapy may lead to poor outcome. Case presentation: This paper describes a case of anti‐N‐methyl‐D‐aspartate receptor (anti‐NMDAR) encephalitis in a young female who presented with a short prodrome; had a rapidly progressive illness; and could not be saved even after early, optimal, and aggressive immunomodulatory therapy. Conclusions: Despite early diagnosis, and prompt therapy, anti‐NMDAR encephalitis may progress and remain refractory to treatment. More studies are needed for further therapeutic avenues in treatment‐refractory cases of anti‐NMDAR encephalitis not responding even to cyclophosphamide as highlighted by our case. Abstract : This paper describes a case of anti‐N‐methyl‐D‐aspartate receptor (anti‐NMDAR) encephalitis with rapidly progressive illness refractory to immunotherapy.